Produção e consumo do reggae das radiolas em São Luís/MA: significados, simbolismos e aspectos mercadológicos - Santos, Fabio Abreu (2011)
This study aims to understand the relations of production and consumption in the world of reggae sound systems, identifying meanings, symbolisms and marketing aspects, from its operations in the city of São Luís. Based on the dynamics and structure of the reggae movement in Brazil and in the world and based on the discussions and theoretical approaches that give substance to the understanding of the relationship between culture and consumption in the context of the commodification of cultural products, an immersion in aspects involving the production of reggae sound systems, to identify the meanings designed from the products offered and practices from the production of these enterprises, as well as symbolic aspects existing in the forms of consumption of the product by the reggae public. The choice of participant observation as a methodological approach, made on account of the need to seek a partial or complete description of situations in order to identify specific aspects and operations of sound systems as cultural products, whose representations, from the relational interactions between producers and consumers of their offerings, cause a large repertoire of symbols and meanings that have properly identified and analyzed to understand the dynamics of marketing projects and their impacts in the city of São Luís / MA. Thus, the discourse of informants, treated under the guidance of the method of discourse analysis, allowed the identification of aspects, whose peculiarities have to understand the nature of identity reggae movement in the city and their role of this process as contributors. In general, the research results shows that the produced by reggae sound systems, since its initial design, includes a dynamic system, producing a network of symbols and meanings that shape the relations of the market, involving images, types of communication and a peculiar way of consumption by reggae public of São Luís.